Syphilis epidemiology in 1994–2013, molecular epidemiological strain typing and determination of macrolide resistance in Treponema pallidum in 2013–2014 in Tuva Republic, Russia. Issue 7 (22nd April 2016) - Khairullin, Rafil; Vorobyev, Denis; Obukhov, Andrey; Kuular, Ural‐Herel; Kubanova, Anna; Kubanov, Alexey; Unemo, Magnus
Abstract : The incidence of syphilis in the Tuva Republic (geographical centre of Asia), Russia has been exceedingly high historically. No detailed examinations and no molecular investigations of Treponema pallidum strains transmitted in the Tuva Republic, or in general, in Russia, were published internationally. We examined the syphilis epidemiology in 1994–2013, and the molecular epidemiology and macrolide resistance in T. pallidum strains in 2013–2014 in the Tuva Republic. Among 95 mainly primary or secondary syphilis patients, the arp, tpr, tp0548 and 23S rRNA genes in 85 polA gene‐positive genital ulcer specimens were characterized. The syphilis incidence in Tuva Republic peaked in 1998 (1562), however declined to 177 in 2013. Among the 70 (82%) completely genotyped specimens, six molecular strain types were found. Strain type 14d/f accounted for 91%, but also 14c/f, 14d/g, 14b/f, 14i/f, 9d/f, and 4d/f were identified. Two (2.4%) specimens contained the 23S rRNA A2058G macrolide resistance mutation. This is the first internationally published typing study regarding T. pallidum in Russia, performed in the Tuva Republic with the highest syphilis incidence in Russia. The two molecular strain types 4d/f and 9d/f have previously been described only in Eastern and Northern China and for the first time, macrolide‐resistant syphilis was described in Russia.